The Impact of the COVID-19 Pandemic on the Development of Internal Tourism in the Russian Federation: A Statistical Analysis - KABANOVA, Elena Evgen'evna; VETROVA, Ekaterina Alexandrovna; EVSTRATOVA, Tatiana Anatolyevna; BOGACHEVA, Tatiana Vyacheslavovna; KUBASOVA, Elena Ivanovna (Journal of Environmental Management and Tourism, 2021)
The purpose of this paper is to determine the impact of the COVID-19 pandemic on the development of internal tourism in the Russian Federation, identify the prerequisites and analyze the factors limiting the development of internal tourism. Monitoring of the tourism potential of the Russian Federation and analysis of the resource base made it possible to assess the existing problems and suggest possible ways to solve them. The authors have determined the prerequisites for the development of internal tourism during the pandemic on the territory of Russia, observed the place and specifics of internal tourism in tourist flows, and substantiated the place and role of the pandemic in the development of internal tourism in the Russian Federation. As a result of the study, the trends in the development of internal tourism have been identified, as well as the regions of its most promising development and the constraining factors for the development of internal tourism. The results obtained contribute to the development of internal tourism in the Russian Federation, the popularization of internal tourism online, which ultimately ensures an increase in the tourist flow within the country, and also allows creating additional jobs in the tourism sector .